Manufacturing of Bricks in the Past, in the Present and in the Future: A state of the Art Review - Alaa A. Shakir; Ali Ahmed Mohammed (Institute of Advanced Engineering and Science, 2013)
The most basic building material for construction of houses is the conventional brick. The rapid growth in today’s construction industry has obliged the civil engineers in searching for more efficient and durable alternatives far beyond the limitations of the conventional brick production. A number of studies had taken serious steps in manufacturing bricks from several of waste materials. However, the traditional mean of bricks production which has brought hazardous impacts to the context has not yet been changed or replaced by more efficient and sustainable one. This paper aims to compile this state of the art work of manufacturing bricks in the past and the current trend in the bricks industry with respect to the raw materials, ways of manufacturing and the out- comings. Moreover, the hazardous impacts of the conventional brick manufacturing will be wholly covered as well as the attempts of the previous researches in treating the problem properly. This paper is an attempt to fill the gap of the past studies and suggest more sustainable and sophisticated methods of brick manufacturing in the future.